Current options and recommendations for the use of thoracic endovascular aortic repair in acute and chronic thoracic aortic disease: an expert consensus document of the European Society for Cardiology (ESC) Working Group of Cardiovascular Surgery, the ESC Working Group on Aorta and Peripheral Vascular Diseases, the European Association of Percutaneous Cardiovascular Interventions (EAPCI) of the ESC and the European Association for Cardio-Thoracic Surgery (EACTS). (4th October 2020) - Czerny, Martin; Pacini, Davide; Aboyans, Victor; Al-Attar, Nawwar; Eggebrecht, Holger; Evangelista, Arturo; Grabenwöger, Martin; Stabile, Eugenio; Kolowca, Maciej; Lescan, Mario; Micari, Antonio; Muneretto, Claudio; et al.
Abstract: Since its clinical implementation in the late nineties, thoracic endovascular aortic repair (TEVAR) has become the standard treatment of several acute and chronic diseases of the thoracic aorta. While TEVAR has been embraced by many, this disruptive technology has also stimulated the continuing evolution of open surgery, which became even more important as late TEVAR failures do need open surgical correction justifying the need to unite both treatment options under one umbrella. This fact shows the importance of—in analogy to the heart team—aortic centre formation and centralization of care, which stimulates continuing development and improves outcome . The next frontier to be explored is the most proximal component of the aorta—the aortic root, in particular in acute type A aortic dissection—which remains the main challenge for the years to come. The aim of this document is to provide the reader with a synopsis of current evidence regarding the use or non-use of TEVAR in acute and chronic thoracic aortic disease, to share latest recommendations for a modified terminology and for reporting standards and finally to provide a glimpse into future developments.